POTENTIAL MARINE-DERIVED FUNGI ISOLATED FROM SPONGE IN PRODUCE NEW AND BENEFICIAL COMPOUNDS - Tanod, Wendy Alexander; Muliadin, Muliadin; Adel, Yeldi S; Dewanto, Didit Kustantio (KAUDERNI : Journal of Fisheries, Marine and Aquatic Science, 2020)
Marine organisms are a source of natural products and produce compounds with a molecular structure that is unique and useful. Thousands of new compounds have biological activitity for anticancer, antiviral, and antimicrobial. This compounds isolated from various marine organism, including from marine-derived fungi. Investigation of chemical compounds from marine-derived fungi isolated from sponge has increased steadily, indicating the important role of marine-derived fungi in the discovery of drug compounds. The sponge has produced various kinds of fungi, which have reported to provide a variety of pharmacologically active metabolites and structurally diverse. Study literature showed that many fungal genera isolated from the marine sponge dominated the genus Acremonium, Aspergillus, Penicillium, Phoma, and Fusarium. The high proportion of genera and new compounds showed that the fungi isolated from the sponge could develop.